Racism, not race : answers to frequently asked questions - Graves, Joseph L., 1955-; Goodman, Alan H. (Columbia University Press, 2022)
"We talk a lot about race, yet we rarely focus on the underlying question of what race is and its connections to racism. Conversations about race can be uncomfortable and confusing, but this is resolvable if we ask the right questions and focus on clear answers. What, exactly, is race? Joseph L. Graves and Alan H. Goodman illuminate the idea of race so that people who want to confront the topic of racial injustice can do so with the necessary conceptual tools. Most people think race is real, they argue, and it is. But race is not real in the way that most of us have grown up to think of it. Race is not natural, fixed, or based on biology. Instead, they continue, racism created the idea of race, the idea of race has real effects, and while human genetic variation is biologically real, it is not race. The book is based on evidence from biological and social science. It is composed of twelve question-begging chapters, which engage topics such as the origins of race, race and genetics, the forms of racism, race and health, race and ability, institutional racism, DNA and ancestry testing, "race mixing," race and politics, and what it means to be an antiracist. The book is ideally suited for people want to understand more about what race is, where it came from, and how to confront its pernicious effects, in a format that is clear, direct, and can be used as a model to defend one's antiracist position"--